1995
DOI: 10.1677/joe.0.1460227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of growth hormone-releasing hormone and hexarelin, a novel growth hormone-releasing peptide-6 analog, on growth hormone secretion in humans with or without glucocorticoid excess

Abstract: The aim of our study was to investigate the effect of hexarelin, a novel GH-releasing peptide-6 analog, and GH-releasing hormone (GHRH) (alone or in combination) on GH secretion in adult patients with increased somatostatin tone due to chronic glucocorticoid excess. We studied seven adult patients undergoing long-term (no less than 6 months) immunosuppressive glucocorticoid treatment for non-endocrine diseases (six females and one male, age range 42-68 years) and one subject (female, age 31 years) with endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
3
13
1
Order By: Relevance
“…Concerning GH release, our data, showing that pretreatment with 1 mg DEXA on the previous night does not modify the somatotrope responsiveness to HEX, do not disagree with previous data showing that the GH response to GHRPs is only blunted after exposure to exogenous corticosteroids [23, 24, 30], while it is more clearly inhibited in patients with Cushing’s syndrome [8, 44]. Moreover, glucocorticoids are even able to stimulate GH secretion in different experimental conditions, and it has been clearly demonstrated that their effects on somatotrope secretion depend on dose, time and length of exposure [30, 31].…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Concerning GH release, our data, showing that pretreatment with 1 mg DEXA on the previous night does not modify the somatotrope responsiveness to HEX, do not disagree with previous data showing that the GH response to GHRPs is only blunted after exposure to exogenous corticosteroids [23, 24, 30], while it is more clearly inhibited in patients with Cushing’s syndrome [8, 44]. Moreover, glucocorticoids are even able to stimulate GH secretion in different experimental conditions, and it has been clearly demonstrated that their effects on somatotrope secretion depend on dose, time and length of exposure [30, 31].…”
Section: Discussioncontrasting
confidence: 47%
“…In fact, the GH-releasing effect of GHRPs is strongly reduced, though not lost, in presence of hypothalamo-pituitary disconnection [15, 19, 20]. On the other hand, it has also been shown that the stimulatory effect of GHRPs on GH secretion is, at least partially, refractory to inhibitory influences including neurotransmitters, glucocorticoids, glucose, lipids and even exogenous somatostatin and rhGH [21, 22, 23, 24, 25, 26]. …”
Section: Introductionmentioning
confidence: 99%
“…We found that the GH response to HEX in hypocortisolemic patients with AD is preserved and similar to that in NS even after metyrapone or RU-486 pretreatment. There is evidence that the GH response to GHS is not affected by acute dexamethasone pretreatment [30]while it is only blunted by prolonged and chronic corticosteroid exposure [44, 45]. These findings agree with the assumption that the GH-releasing activity of GHS is generally refractory to inhibitory and stimulatory inputs [2, 23], which are very active in inhibiting and enhancing, respectively, the GH response to GHRH [46].…”
Section: Discussionsupporting
confidence: 59%
“…It is a classic observation that chronic hypercortisolism inhibits somatic growth as well as GH secretion [25, 26]. In Cushing’s syndrome, GH responses appear blunted towards all stimuli tested so far [27, 28]; ghrelin can now be added to this list.…”
Section: Discussionmentioning
confidence: 99%